Hydroisomerization of n-Hexadecane Over Nickel-Modified SAPO-11 Molecular Sieve-Supported NiWS Catalysts: Effects of Modification Methods - Dai, Xiaojun; Cheng, Yan; Si, Meng; Wei, Qiang; Zhou, Yasong (Frontiers in Chemistry, 2022)
The complexation-excessive impregnation modification method, which was original in this study, and the ion-exchange method and the in situ modification method were used to synthesize Ni-modified SAPO-11 molecular sieves. With the Ni-modified SAPO-11 samples as support, the corresponding NiWS-supported catalysts for the hydroisomerization of n-hexadecane were prepared. The effects of Ni-modification on SAPO-11 characteristics and the active phase were studied. The structure, morphology, and acidity of SAPO-11, as well as the interaction between active metals and support, the morphology, dispersibility, and stacking number of the active phase, were all changed by Ni-modification methods. The complexation-excessive impregnation modification method deleted a portion of Al from SAPO-11 molecular sieves while simultaneously integrating Ni into the skeletal structure of the surface layer of SAPO-11 molecular sieves, considerably enhancing the acidity of SAPO-11 molecular sieves. Furthermore, during dealumination, ethylenediaminetetraacetic acid generated more mesoporous structures and increased the mesoporous volume of SAPO-11 molecular sieves. Because the complexation-excessive impregnation modification method increased the amount of Ni in the surface framework of the SAPO-11 molecular sieve, it has weakened the interaction between the active phase and the support, improved the properties of the active phase, and greatly improved the hydroisomerization performance of NiW/NiSAPO-11. The yield of i-hexadecane of NiW/NiSAPO-11 increased by 39.3% when compared to NiW/NiSAPO-11. It presented a realistic approach for increasing the acidity of SAPO-11, reducing the interaction between active metals and support, and improving the active phase stacking problem.